2019
DOI: 10.31235/osf.io/t64sy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Register Analysis and Synthesis

Abstract: The study of register in computational language research has historically been divided into register analysis, seeking to determine the registerial character of a text or corpus, and register synthesis, seeking to generate a text in a desired register. This article surveys the different approaches to these disparate tasks. Register synthesis has tended to use more theoretically articulated notions of register and genre than analysis work, which often seeks to categorize on the basis of intuitive and somewhat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…The term 'register' defines the situational context of communication (Biber & Conrad 2005). Registers are thus primarily differentiated in non-linguistic terms, although linguistic variability can be observed when comparing different registers with each other (Argamon 2019;Biber & Conrad 2005). Contributing factors to register variation (amongst others) are situational characteristics such as the setting and channel of communication, discourse participants and their relationships, as well as the purpose of communication (Biber & Conrad 2019), which might require certain linguistic features in order to be successful.…”
Section: Defining Registermentioning
confidence: 99%
“…The term 'register' defines the situational context of communication (Biber & Conrad 2005). Registers are thus primarily differentiated in non-linguistic terms, although linguistic variability can be observed when comparing different registers with each other (Argamon 2019;Biber & Conrad 2005). Contributing factors to register variation (amongst others) are situational characteristics such as the setting and channel of communication, discourse participants and their relationships, as well as the purpose of communication (Biber & Conrad 2019), which might require certain linguistic features in order to be successful.…”
Section: Defining Registermentioning
confidence: 99%
“…This section describes the key differences of this study from other studies in Automatic Genre Identification (AGI) and Multi-Dimensional Analysis (MDA). The main aim of AGI studies is to predict stylistic properties using extractable features (Santini et al, 2010;Argamon, 2019). Experiments have been carried out with such features as POS tags (Karlgren and Cutting, 1994), broader linguistic features (Kessler et al, 1997), including theoretically motivated features from Systemic-Functional Linguistics (Argamon et al, 2007).…”
Section: Related Studies On Computational Analysis Of Genresmentioning
confidence: 99%
“…It has been shown that the use of topic modelling helps in finding the differences between the Web corpora (Fothergill et al, 2016;Sharoff, 2013). Since the arrival of machine learning methods in the 1990s, genre classification and related approaches to classification of texts with respect to their stylistic features developed from (Karlgren and Cutting, 1994) to (Pritsos and Stamatatos, 2018), see a recent overview in (Argamon, 2019). However, genre classification methods have not been yet applied to very large corpora from the Web.…”
Section: Related Studiesmentioning
confidence: 99%